2011
DOI: 10.1002/anie.201101040
|View full text |Cite
|
Sign up to set email alerts
|

The Thermodynamically Stable Form of Solid Barbituric Acid: The Enol Tautomer

Abstract: Stabilizing the unstable: In textbooks barbituric acid is always drawn in its keto tautomeric form, which is indeed preferred in solution and in most polymorphic phases. However, phase IV, obtained by grinding, consists of molecules in the enol form, as shown by neutron powder diffraction. This phase is found to be the most stable one at room temperature; the “unstable” enol tautomer is stabilized by a higher number of hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
84
0
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 19 publications
10
84
0
5
Order By: Relevance
“…Such a strong kinetic hindrance was observed, e.g. for the thermodynamically stable phase of barbituric acid, which is formed only by grinding and has never be found in (re)crystallisation experiments; even phase transition in suspension works only, if seed crystals of the thermodynamically stable phase are present [50]. In order to investigate, if 3 could crystallise in the same structure as 1, and if 4 could adopt the same structures as 1, 2 or 3, additional grinding and slurry experiments were performed on 3 and 4 by heterogenous seeding with 5% of crystals of the corresponding derivatives.…”
Section: Resultsmentioning
confidence: 93%
“…Such a strong kinetic hindrance was observed, e.g. for the thermodynamically stable phase of barbituric acid, which is formed only by grinding and has never be found in (re)crystallisation experiments; even phase transition in suspension works only, if seed crystals of the thermodynamically stable phase are present [50]. In order to investigate, if 3 could crystallise in the same structure as 1, and if 4 could adopt the same structures as 1, 2 or 3, additional grinding and slurry experiments were performed on 3 and 4 by heterogenous seeding with 5% of crystals of the corresponding derivatives.…”
Section: Resultsmentioning
confidence: 93%
“…[9] Crystal growth from ethanol solution using as imilar procedure resulted in crystals with the same density as those from methanol. This is 3-4-fold below saturation at 60 8 8C.…”
mentioning
confidence: 99%
“…[4][5][6][7] Ball-mill grinding experiments showed that atautomeric form can be prepared in this fashion. [9] Slurry experiments in methanol, ethanol, and butanol showed that this alternative tautomeric polymorph is the thermodynamically stable form. [2].Itwas,however,inferred from X-ray and neutron powder diffraction data that this tautomeric form is the enol structure (2;F igure 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations